Moral Tuning. (24th July 2018) - Sivertsen, Sveinung Sundfør; Halstead, Jill; Slaattelid, Rasmus T.
Abstract: Can a set of musical metaphors in a treatise on ethics reveal something about the nature and source of moral autonomy? This article argues that it can. It shows how metaphorical usage of words like tone, pitch, and concord in Adam Smith's Theory of Moral Sentiments can be understood as elements of an analogical model for morality. What this model tells us about morality depends on how we conceptualise music. In contrast to earlier interpretations of Smith's metaphors that have seen music as an aesthetic object, this article sees music as a practice. Understood in this way, the analogy allows us to see morality too as a practice––as moral tuning . This in turn reveals a novel answer to the intractable problem of conventionalism: moral autonomy consists in the freedom inherent in the constant need to interpret and reinterpret the strictly formal ideal of perfect propriety.